ChemInform Abstract: Regioselective Synthesis of 1, 2‐Dihydroquinolines by a Solvent‐Free MgBr2‐Catalyzed Multicomponent Reaction. Issue 10 (11th March 2014) - Gutierrez, Rsuini U.; Correa, Hans C.; Bautista, Rafael; Vargas, Jose Luis; Jerezano, Alberto V.; Delgado, Francisco; Tamariz, Joaquin
Abstract The title reaction is catalyzed by magnesium bromide and carried out under solvent‐free conditions.